Land use and cover change (LUCC) impacts on Earth's eco-environments: Research progress and prospects. Issue 3 (1st February 2023) - Feng, Huihui; Wang, Shu; Zou, Bin; Nie, Yunfeng; Ye, Shuchao; Ding, Ying; Zhu, Sijia
Highlights: It summarized research progress and prospects of LUCC impacts on eco-environments. LUCC affects Earth's eco-environment by altering the surface-atmospheric interaction. Mechanisms of LUCC impacts are surface radiation budget and matter conservation. Challenges remain because of uncertainties in data, methodologies and evolution. Future studies on data assimilation, contribution, physical and full-process are required. Abstract: Land use and cover change (LUCC) is one of the key variables dominating land–atmosphere interactions and strongly affects the Earth's eco-environments by altering surface properties. Numerous studies have been carried out to assess the impact of LUCC. However, the Earth is a large, open and complex system characterized by complex interactions between its eco-environments and drivers. This study aimed to summarize previous studies of the impact of LUCC on the Earth's eco-environments and discuss the progress and limitations in suggesting future directions. Previous studies have confirmed that LUCC has a wide range of impacts on the Earth's eco-environments, which are represented by the alternation of climate (temperature, precipitation, wind, and humidity), hydrology (soil moisture, runoff, and evapotranspiration), ecology and environmental (air, water, and soil) pollution. Physically, the impacts were mainly attributed to the disturbance of the surface radiation budget and matter conservation caused by LUCC. Although great achievements have been made, several challenges remain because of the unavoidable uncertainties in data sources and methodologies and the complexity of eco-environmental evolution. Therefore, data assimilation, physical-based investigations, contribution isolation, and full-process analysis are required to overcome these challenges in future research. The results of this study helped to capture the impact of LUCC and its physical mechanisms, which provide useful clues for future research and support the relative land use management for sustainable development.